PENGARUH MODEL PROBLEM BASED LEARNING TERHADAP HASIL BELAJAR SUBTEMA MANUSIA DAN BENDA DI LINGKUNGANNYA - Hilda Sovia Marwah; Yudhie Suchyadi; Tri Mahajani (Journal of Social Studies, Arts and Humanities (JSSAH), 2021)
THE EFFECT OF PROBLEM BASED LEARNING MODEL ON LEARNING OUTCOMES OF HUMANS AND OBJECTS IN THEIR ENVIRONMENTThis research aims to determine the effect of the Problem Based Learning Model on Learning Outcomes of the Human and Objects Subtheme in their Environment in class V of SDN Duta Pakuan Bogor City for the 2020/2021 academic year. This study uses a quantitative research method through a two-group design quasi-experimental approach with Simple Random Sampling. The analytical technique used is the analysis prerequisite test which includes normality test, homogeneity test of variance, and hypothesis testing using t test. The results of the study show that there is an effect of the Problem Based Learning Model on the Learning Outcomes of Humans and Objects in their Environment. This can be seen from the N-Gain in the experimental class group of 82, while the control class group got an N-Gain value of 73. The completeness of learning outcomes obtained by the experimental group was 94% while in the control class group it was 77%. And the results of hypothesis testing that H0 is rejected and Ha is accepted because tcount (2,64697) ttable (2,00030). With this it can be concluded that the research has a positive and significant influence between "The Effect of Problem Based Learning Models on Learning Outcomes of Humans and Objects in their Environment". The results of this study are expected to provide new knowledge regarding the application of innovative learning models that can improve learning outcomes.